Identification and characterization of violence in school: subsidies for prevention and confrontation actions - Tavares Gontijo, Daniela; Julião, Claudia Helena; Borges Kappel, Verônica; Castro Alves, Heliana; Farinelli, Marta Regina (O Mundo da Saúde, 2013)
Violence in schools is a violation of rights of children / adolescents. The aim of this work was to identify and try to characterize a typology of the occurrence of violence in public schools. It was a census study conducted in 27 public schools, having as subjects 1042 students. Data were collected by means of a self-administered questionnaire and analyzed by descriptive statistics. Violence was present in the school routine, mainly through episodes of psychological and physical aggression. The episodes characterized situations of violence at school, against the school and coming from the school, a school in which students and teachers are pointed at either as victims or perpetrators. We emphasize the need of intersectorial actions to confront the violence in the school.